CFD Study of Aerodynamics Aspect on Isuzu NLR 55 TX Truck - - Nim: 13114082, FEBRIZAL
Reduction of the drag coefficient is one way to improve truck performance. The purpose of this research is to model and conduct aerodynamic behavior in Isuzu NLR 55 TX truck. Characteristics of aerodynamics on trucks can be controlled using additional devices. The enhancements are cabroof, baseplate and frame extension. A computational fluid dynamics (CFD) calculation on the Isuzu NLR 55 TX truck model is performed to simulate and estimate the coefficient drag (CD) using Ansys Fluent. The speed of a truck vehicle is varied between speeds of 20 km/h up to a speed of 90 km/h. The k-omega SST turbulence model was chosen as the best turbulence model in this simulation.The modeling of the combination truck cabroof-baseplate and cabroof-frame extension was also carried out in this study. Each model of the truck is done simulation process to get speed and pressure contour so it can know what phenomenon happened. From the simulation results, it can be concluded that the vector plot of the flow velocity formed to get different results each model. The aerodynamic resistance of the truck starts to affect the speed of 80 km /jam. The highest CD is generated by the standard truck model of 0.66, and the lowest CD value in the cabroof-frame extension combination truck is 0.36.